2022
DOI: 10.2147/opth.s357267
|View full text |Cite
|
Sign up to set email alerts
|

First Real-World, Multicenter, Post-Marketing, Retrospective Study of Dexamethasone Intraocular Suspension for Inflammation After Cataract Surgery

Abstract: Purpose To evaluate dexamethasone intraocular suspension 9% (intraocular DXM) in real-world clinical use to manage inflammation associated with cataract surgery. Setting Patients who underwent cataract surgery and received intraocular DXM at 22 outpatient eye surgery centers in the US. Design Retrospective, observational chart review. Methods Records of all patients who received intraocular DXM from March to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Matossian and others [104 ▪▪ ] in their randomized clinical study showed that dexamethasone intraocular suspension was as effective as topical prednisolone drops and the rise of IOP was comparable between the groups. A recent study by Bacharach et al was the first real-world multicentre postmarketing study, in which results were similar to previous clinical trials: dexamethasone intraocular suspension was effective in inflammation control, adverse reactions were rare and mostly mild-to-moderate from which the most common was raised IOP (7 reported events from 527 patients), which showed that suspension is effective and well tolerated [105 ▪ ].…”
Section: Management Of Inflammation With the Dropless Cataract Surgerysupporting
confidence: 68%
“…Matossian and others [104 ▪▪ ] in their randomized clinical study showed that dexamethasone intraocular suspension was as effective as topical prednisolone drops and the rise of IOP was comparable between the groups. A recent study by Bacharach et al was the first real-world multicentre postmarketing study, in which results were similar to previous clinical trials: dexamethasone intraocular suspension was effective in inflammation control, adverse reactions were rare and mostly mild-to-moderate from which the most common was raised IOP (7 reported events from 527 patients), which showed that suspension is effective and well tolerated [105 ▪ ].…”
Section: Management Of Inflammation With the Dropless Cataract Surgerysupporting
confidence: 68%
“…3 These findings are in alignment with a real-world observational study on the dexamethasone intraocular suspension 9%, where an ACC grade of 0 was achieved by 49/71 patients (69%) at Day 8 and 30/32 patients (93.7%) at Day 14 for patients who received intraocular dexamethasone only. 59 Lee et al evaluated a different formulation of dexamethasone (an intracanalicular plug) and found more patients with complete ACC clearance at Day 8 (22.4%) and at Day 14 (42.7%) than placebo; 60 our study had a much higher percentage at Day 8 (33.3%) and at Day 15 (66.7%). Pain scores fared similarly: at Day 8, 79.2% and at Day 14, 80.6% were pain free with the insert 60 (in our study, 82.1% at Day 8 and 89.7% at Day 15 were pain-free).…”
Section: Discussionmentioning
confidence: 45%
“… 3 These findings are in alignment with a real-world observational study on the dexamethasone intraocular suspension 9%, where an ACC grade of 0 was achieved by 49/71 patients (69%) at Day 8 and 30/32 patients (93.7%) at Day 14 for patients who received intraocular dexamethasone only. 59 …”
Section: Discussionmentioning
confidence: 99%